The making of the Ti-6Al-4V alloy by electrolysis of compounded solid oxide precursors in molten calcium chloride - Ma, Mingchan (2021)
Titanium is known as the ‘wonder metal’ because of its exceptional specific strength, light weight, excellent corrosion resistance, and outstanding biocompatibility. However, the use of this metal is limited in niche markets (e.g. aerospace industries, and biomedical applications) due to its inherent costliness. Since titanium is the fourth abundant structural metal in the earth’s crust, its high cost is due mainly to the complex extraction and downstream alloying processes involved in its production. Accordingly, there is a need for the development of new processes or the optimisation of existing methods to reduce the cost of production, and to encourage its widespread application. Among all novel processes, the FFC-Cambridge Process is one of the most promising methods to produce cost-effective titanium materials. This process is capable of producing titanium and other metals from the direct electrochemical deoxidation of metal oxides in molten electrolyte. This dissertation focuses on the optimisation of the FFC-Cambridge Process by using a compounded solid oxide precursor to produce Ti-6Al-4V alloy. This compounded metal oxides containing co-oxides were prepared by vacuum-sintering the metal oxide mixtures at high temperatures. The main hypothesis is that the electrolysis of this compounded solid oxide precursor would be beneficial to improve the current efficiency compared with that for the electrolysis of the precursor without co-oxides, as the former would render higher electrical conductivity and suppress the formation of perovskite (i.e. CaδTiOy, y/δ≥2). The material properties of the as-received metal oxides (i.e. TiO2, Al2O3, and V2O3), binary (i.e. TiO2-V2O3, TiO2-Al2O3, and Al2O3-V2O3) and ternary (i.e. TiO2-Al2O3- V2O3) metal oxide mixtures, and compounded metal oxides formed from these mixtures have been rigorously characterised through Scanning Electron Microscopy (SEM), Energy-Dispersive X-ray Spectroscopy (EDS), and X-ray Diffraction (XRD). Major findings revealed that vacuum-sintering TiO2-V2O3 at 1300℃, and TiO2-Al2O3 at 1500℃ results in the formation of metal co-oxides including V3Ti6O17 and Al2TiO5, respectively. Furthermore, cyclic voltammetry and electrical conductivity tests have been carried out on these as-received materials, binary and ternary oxide mixtures, and the compounded solid oxides containing co-oxides. The results demonstrated that both the existence of V3Ti6O17 and Al2TiO5 are able to improve the electrical conductivity compared with the simply-mixed metal oxide mixtures, while the compounded solid oxide precursor containing V3Ti6O17 exhibit higher electrical conductivity than that containing Al2TiO5 (the electrical conductivity of former is 7.015Ω-1•m, and that of the latter is 1.953Ω-1•m). Based on these findings, ternary TiO2-Al2O3-V2O3 was vacuum-sintered at 1300℃ to form V3Ti6O17 and Al2TiO5. The XRD pattern shows the existence of TiO2, V3Ti6O17 and trace amount of Al2O3 and Al2TiO5 after sintering. Ti-6Al-4V alloy has been successfully produced from the 24h constant-voltage (i.e. 3.2V) electrolysis of this compounded solid oxide precursor in molten CaCl2 at 900℃. The oxygen content of the electrolytic product was examined by Inert Gas Fusion Analysis (IGFA) with the result of 2000 ppm. The distribution of alloying elements across the produced Ti-6Al-4V alloy has been proven to be homogeneous by elemental mapping. In contrast, the oxygen content of the electrolytic product from 24h electrolysis of TiO2-Al2O3-V2O3 mixture was 2800 ppm, which is slightly higher that of the electrolytic product from the compounded precursor. The current efficiency recorded during the electrolysis of this compounded solid oxide precursor was calculated to be 17% (with background current). This is 1.3 times the current efficiency of 13% for the electrolysis of the TiO2-Al2O3-V2O3 oxide mixture. Additionally, the energy consumed in the 24h electrolysis of this compounded solid oxide precursor (containing metal oxides plus co-oxides) was calculated to be 36.18 kWh/kg-Ti alloy. This is lower than the value (i.e. 47.53 kWh/kg-Ti alloy) recorded in the electrolysis of TiO2-Al2O3-V2O3 mixture. Therefore, it can be concluded that the use of this compounded solid oxide precursor can significantly increase the electrolysis efficiency, and reduced the energy consumption of the FFC-Cambridge Process for the production of Ti-6Al-4V alloy. Accordingly, findings from this research have provided a new research direction focusing on the utilisation of this compounded solid oxide precursor to further enhance the FFC-Cambridge Process for fabricating alloys.